2009
DOI: 10.1350/ijps.2009.11.1.112
|View full text |Cite
|
Sign up to set email alerts
|

Illegal Drug Use by Police Officers: Using Research and Investigations to Inform Prevention Strategies1

Abstract: Illegal drug use by police officers is a concern in many jurisdictions. The Police Integrity Commission, an independent oversight agency in New South Wales, Australia, conducted a large-scale project on the use of illegal drugs by some NSW police officers. This project, codenamed Operation Abelia, sought to provide a better understanding of the nature of the problem of officer illegal drug use and to identify what can be done to minimise such illegal drug use. This paper outlines how research and investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…While there is noteworthy research among Australian policing jurisdictions, data is typically sourced externally to policing agencies (Goodman-Delahunty 2014; Crehan 2019), utilising qualitative methodologies (Hine et al 2018), or small samples (People 2008;People et al 2010;Gorta 2009). While these studies provide insight into the misconduct environment, there is a paucity of empirical analysis of substantial police misconduct datasets.…”
Section: New South Wales Policing Jurisdictionmentioning
confidence: 99%
“…While there is noteworthy research among Australian policing jurisdictions, data is typically sourced externally to policing agencies (Goodman-Delahunty 2014; Crehan 2019), utilising qualitative methodologies (Hine et al 2018), or small samples (People 2008;People et al 2010;Gorta 2009). While these studies provide insight into the misconduct environment, there is a paucity of empirical analysis of substantial police misconduct datasets.…”
Section: New South Wales Policing Jurisdictionmentioning
confidence: 99%
“…Over 81 percent of the positive tests in Boston involved the use of cocaine, and police executives indicated that they believed cocaine had surpassed marijuana as the drug of choice among police (Smalley 2006). More recent data derived from self-report surveys of officers in a single agency in Australia suggest that police use a wider variety of drugs including marijuana, amphetamines, cocaine, ecstasy, heroine, ketamine, and non-prescribed steroids (Gorta 2009). Lersch and Mieczkowski (2005a) report results of drug tests conducted in a large police agency in the Eastern United States in which very few officers tested positive.…”
Section: Drug-related Police Crimementioning
confidence: 99%
“…As in all professions, however, a small number of employees fail to meet ethical and legal standards. Previous research has documented a wide variety of police crime and corruption including perjury, bribery, extortion, robbery, burglary, drug use, domestic assault, and brutality (Barker & Carter, 1994;Gorta, 2009;Kappeler, Sluder, & Alpert, 1998;McDowell, 1984;Miller & Braswell, 1985;Reiss, 1971;Roebuck & Barker, 1974;Sherman, 1981).…”
mentioning
confidence: 99%